Automated pallets tracking system for manufacturing assembly area - Zamzuri, Hassan (2013)
Efficiency in production job floor is a very important element for manufacturer to keep their company competitive. A good material handling system and good inventory control system are some of the factors that can contribute to high efficiency of production job floor.The purpose of this study is to solve a real industry-related problem in material handling that affect production efficiency at PHN Industry Sdn Bhd. The roblem currently being faced at PHN is that the pallets are not available at the right time as needed due to the absence of a system that monitors the movement of these pallets based on some pre-define schedules. The problem can be solved by developing an Automated Pallets Tracking System. This study involved software and hardware development. The system used Radio Frequency Identification Devices (RFID) as dentification and tracking device. The Visual Basic Programming is used to design Graphic User Interface (GUI) system while Microsoft SQL is used as pallets database. The Arduino Microcontroller is used as interface medium for RFID system and GUI. The hardware and software components were successfully integrated into a system and the performance is validated. The validation results showed the capability of the system to identify and track pallets in real-time. However, several modifications and improvements are desired before the system could be applied in actual industrial environment.